2006
DOI: 10.1677/joe.1.06165
|View full text |Cite
|
Sign up to set email alerts
|

Estrous cycle dependent changes in expression and distribution of Fas, Fas ligand, Bcl-2, Bax, and pro- and active caspase-3 in the rat ovary

Abstract: In the present investigation, the localization of proteins involved in ovarian apoptosis were studied throughout the estrous cycle in the presence of fluctuating hormone levels. Fas, Fas ligand, Bcl-2, Bax and caspase-3 mRNA expression and proteins were detected in all ovarian tissue extracts, though the amount of protein varied with the phase of the estrous cycle. Fas, Bax and caspase-3 protein levels were highest at diestrus and decreased thereafter towards metestrus. In contrast, Fas ligand and Bcl-2 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 82 publications
5
61
1
1
Order By: Relevance
“…Immunohistochemistry data demonstrate that most of these proteomic changes are evident in both LLC and SLC on day 16 of the estrous cycle or pregnancy. Previous studies clearly indicate a role for caspase-3 in luteal cell apoptosis in various species (Carambula et al 2002, Davis & Rueda 2002, Peluffo et al 2005, Yadav et al 2005, Slot et al 2006. Together, present results along with previous findings suggest that activation of caspase-3 dependent as well as independent apoptosis pathways are required for natural luteolysis; whereas, these pathways need to be inhibited or suppressed to maintain the survival of the CL during establishment of pregnancy in sheep.…”
Section: Survival and Apoptosis Proteins In The CLsupporting
confidence: 83%
See 1 more Smart Citation
“…Immunohistochemistry data demonstrate that most of these proteomic changes are evident in both LLC and SLC on day 16 of the estrous cycle or pregnancy. Previous studies clearly indicate a role for caspase-3 in luteal cell apoptosis in various species (Carambula et al 2002, Davis & Rueda 2002, Peluffo et al 2005, Yadav et al 2005, Slot et al 2006. Together, present results along with previous findings suggest that activation of caspase-3 dependent as well as independent apoptosis pathways are required for natural luteolysis; whereas, these pathways need to be inhibited or suppressed to maintain the survival of the CL during establishment of pregnancy in sheep.…”
Section: Survival and Apoptosis Proteins In The CLsupporting
confidence: 83%
“…By contrast, interactions between pro-apoptotic and anti-apoptotic signaling pathways and activation of caspases-3 dependent or independent intrinsic apoptosis pathways determine the death of cells (Adams & Cory 1998, Jiang & Wang 2004. Previous studies have shown that administration PGF 2a regulates genes or protein associated with cell survival and apoptosis in cows (Davis & Rueda 2002, Hou et al 2008, Arvisais et al 2010, Atli et al 2012, sheep (Romero et al 2013), pigs (Diaz et al 2013), rodents (Carambula et al 2002, Slot et al 2006, and primates (Peluffo et al 2005, Yadav et al 2005 during induced luteolysis in vivo and in vitro models. Although there is a large body of information available on induced luteolysis in various species, temporal regulations of cell survival and apoptosis signaling protein machinery in the CL during natural luteolysis and establishment of pregnancy in ruminants are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bid and Bax, Bcl-2 family members, act as proapoptotic factors in the type II pathway [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. These Bcl-2 family members are expressed in the cultured ovarian cells of rodents [50,51] and ovarian tissues of rodents [52,53] and ruminants [54,55]. However, it is not clear whether Bid and Bax are expressed in pig ovaries and involved in granulosa cell apoptosis in porcine follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The binding between the FAS receptor (FAS/CD95), a member of the TNF family, and its ligands (FASLG) leads to the formation of a death-induced signaling complex (Krammer 1999, Slot et al 2006). The BCL2 family might be divided into two main groups, according to their proapoptotic (BAX, BAD, BIM, BclxS, and BOK) or antiapoptotic function (i.e., BCL2, BclxL, and BCL2L2) (Slot et al 2006). All of them are regulatory proteins whose actions occur at the mitochondrial level.…”
Section: R256 H H Ortega and Othersmentioning
confidence: 99%
“…The penultimate stage of cell death requires caspases (Das et al 2008). DNA repair enzymes and cytoskeletal and nuclear scaffold proteins are activated by caspase 3 (Scaffidi et al 1998, Krammer 1999, Slot et al 2006, which is required for apoptosis in follicular atresia. Granulosa cells, oocytes, and theca cells undergo apoptosis as part of atresia (Hsueh et al 1994, Markstrom et al 2002, to which early antral follicles are more sensitive (Markstrom et al 2002).…”
Section: R256 H H Ortega and Othersmentioning
confidence: 99%